2000
DOI: 10.2337/diabetes.49.5.838
|View full text |Cite
|
Sign up to set email alerts
|

Differential brain responses to satiation in obese and lean men.

Abstract: Knowledge of how the brain contributes to the regulation of food intake in humans is limited. We used positron emission tomography and measures of regional cerebral blood flow (rCBF) (a marker of neuronal activity) to describe the functional anatomy of satiation (i.e., the response to a liquid meal) in the context of extreme hunger (36-h fast) in 11 obese (BMI ≥35 kg/m 2 , age 27 ± 5 years, weight 115 ± 11 kg, 38 ± 7% body fat; mean ± SD) and 11 lean (BMI ≤25 kg/m 2 , age 35 ± 8 years, weight 73 ± 9 kg, 19 ± 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
234
7
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(268 citation statements)
references
References 35 publications
23
234
7
4
Order By: Relevance
“…In contrast to the findings of Gautier et al, we did not find correlations between postprandial FFA and activation in hippocampal and parahippocampal regions [28]. Also, there were no significant correlations between glucose and the activation in the limbic system during the fasting and satiated condition when viewing food vs nonfood food pictures.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In contrast to the findings of Gautier et al, we did not find correlations between postprandial FFA and activation in hippocampal and parahippocampal regions [28]. Also, there were no significant correlations between glucose and the activation in the limbic system during the fasting and satiated condition when viewing food vs nonfood food pictures.…”
Section: Discussioncontrasting
confidence: 57%
“…extremely long fasting period as used by others [28]. Also, we performed a second measurement one hour after ingestion of a standardized meal, expecting the acute metabolic and hormonal changes following a meal to be effective in producing a satiated state.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings in adults with obesity indicate greater increases in the PFC and greater decreases in the OFC, amygdala, hippocampus, insula, and temporal lobe during satiation compared to lean individuals Gautier et al, 2000). While these studies examining food motivation in overweight adults aid in the overall understanding of neural mechanisms of overeating and obesity, none have been performed in groups of children and adolescents.…”
Section: Discussionmentioning
confidence: 98%
“…It has been hypothesized that these neural systems also play an important role in controlling hyperphagia in obese individuals (e.g., Tataranni and DelParigi, 2003). Though still in its infancy, neuroimaging research on obese and overweight adults has shown differential patterns of neural activity in obese compared to lean individuals, including abnormal functioning in the hypothalamus (Matsuda et al, 1999), insula Gautier et al, 2000), hippocampus Gautier et al, 2000), and OFC (Gautier et al, 2000). These findings offer evidence for discrepancies in neural circuits involved in food motivation between obese and lean adults.…”
Section: Introductionmentioning
confidence: 99%
“…Differential activations (hyperactivation) have been found in the hypothalamus, 29,30 OFC, 19,30 dorsal striatum, 17 insula 31,32 and hippocampus 31 in obese individuals. Obese adults also show a smaller decrease in hypothalamic activity after a meal when compared with HW individuals.…”
Section: Discussionmentioning
confidence: 99%